2011
DOI: 10.1634/theoncologist.2010-0414
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Acute Organ Toxicity during Intensified Preoperative Radiochemotherapy for Rectal Cancer

Abstract: Learning Objectives After completing this course, the reader will be able to: Describe present strategies of treatment of locally advanced rectal cancer and ongoing clinical trials, including neoadjuvant radiochemotherapy with 50.4 Gy and concomitant 5-FU +/− oxaliplatin.Define the basic clinical parameters, with special emphasis on gender and BMI, correlating with radiochemotherapy-associated side effects in rectal cancer patients and differences in severity of toxicity. CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…This large-scale trial included a sample of 1,688 patients, and results are supported by a smaller scale study (Wolff et al, 2011) that also investigated patients with rectal cancer and used the same tool to measure toxicity. In Wolff et al (2011), almost 4% of the total sample surveyed developed severe grade 4 acute toxicities, which included gastrointestinal, urologic, and dermatologic effects. All affected had a BMI of less than 22, whereas the average BMI for the total sample was 26.4 (Wolff et al, 2011).…”
Section: Discussion Body Mass Indexmentioning
confidence: 77%
See 2 more Smart Citations
“…This large-scale trial included a sample of 1,688 patients, and results are supported by a smaller scale study (Wolff et al, 2011) that also investigated patients with rectal cancer and used the same tool to measure toxicity. In Wolff et al (2011), almost 4% of the total sample surveyed developed severe grade 4 acute toxicities, which included gastrointestinal, urologic, and dermatologic effects. All affected had a BMI of less than 22, whereas the average BMI for the total sample was 26.4 (Wolff et al, 2011).…”
Section: Discussion Body Mass Indexmentioning
confidence: 77%
“…In Wolff et al (2011), almost 4% of the total sample surveyed developed severe grade 4 acute toxicities, which included gastrointestinal, urologic, and dermatologic effects. All affected had a BMI of less than 22, whereas the average BMI for the total sample was 26.4 (Wolff et al, 2011). However, results of a study by Tho et al (2006) indicated no significant correlation between BMI and acute effects of radiotherapy in rectal cancer, although this difference may be attributed to the smaller sample size (41 patients) and, also, the lower dose of radiotherapy received by the sample (45 Gy versus 50.4-54 Gy).…”
Section: Discussion Body Mass Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer metastasis is recognized worldwide to be a major process and as a main reason for high mortality . It is the progressive step, where the spreading of cancer cells occur through circulatory system to distant organs establishing a secondary tumor originated from primary site . The reason behind the organ selectivity is determined by the pattern of blood flow where the provision of a fertile environment compatible tumor cells could grow .…”
Section: Introductionmentioning
confidence: 99%
“…The reason behind the organ selectivity is determined by the pattern of blood flow where the provision of a fertile environment compatible tumor cells could grow . The successful manifestation of metastasis involves primary tumor cell invasion with penetration of small lymphatic or vascular channels, release of neoplastic cells, survival, followed by angiogenesis, and growth at a distant site . Currently, the treatments are unsatisfactory to prolong survival of patients with metastasis .…”
Section: Introductionmentioning
confidence: 99%